2022
DOI: 10.1101/2022.09.20.508664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climate influences bill shape diversification in cavity-excavating birds

Abstract: The remarkable structural and functional diversity of the avian bill serves as an ideal system to understand how ecological and environmental factors influence morphological diversification under physically demanding tasks. For example, in cavity-excavating birds where the bill experiences tremendous physical stresses, climate and habitat affect the mechanical properties of available nesting substrates and therefore can potentially influence the shape and performance of bills. Few studies have focused on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…A similar finding was reported in a study on the functional implications of edentulism in the therizinosaur Erlikosaurus andrewsi , where finite element analysis demonstrated that the presence of a keratinous rhamphotheca enhanced the stress dissipation ability of the skull for different biting scenarios (22). Thus, our study reveals a functional synergy underlying the integrated diversification of the rhamphotheca and bony modules in barbet bills (31).…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…A similar finding was reported in a study on the functional implications of edentulism in the therizinosaur Erlikosaurus andrewsi , where finite element analysis demonstrated that the presence of a keratinous rhamphotheca enhanced the stress dissipation ability of the skull for different biting scenarios (22). Thus, our study reveals a functional synergy underlying the integrated diversification of the rhamphotheca and bony modules in barbet bills (31).…”
Section: Discussionmentioning
confidence: 69%
“…Second, the geometry, excavation performance and behavior of barbet bills may be affected by the mechanical properties of available nesting substrates. African barbets, which occupy drier climatic regimes, exhibit deeper maxillae on average compared to the Asian barbets, which typically reside in more humid, forested regions (31, 32). Because climatic factors like temperature, precipitation and hydrological conditions affect wood decay rates and wood density, we surmise that they may also influence the availability of dead and decaying wood in the habitat (46, 47).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations